Aplikasi Mobile Untuk Pengingat Waktu Kadaluarsa Barang Dalam Kemasan Beserta Peta Distributor - Gebriani Amanda Putri; Juni Nurma Sari; Ibnu Surya (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Expiration date is very important role in determining the quality of goods in containers that are usually sold in supermarkbkets. That items have passed the expiration date if it is used will give a negative effect on the body. But,the Expired date often forgotten, so much stuff that has passed the expiry date is still on the market. So, by using this application is expected to reduce the circulation of goods that have passed expiration dates because this application have alarm which will run 1 month before expired date of the items.This is semi client-server application,where data is retrieved from the server and the entered back into the SQLite database at the client side. This application runs on Android phones as the client and PHP as the server. Client get reported items and distributors data, alarm from items which will expired, stoks charts and can get supplier’s address from maps.This application runs on Android phones as the client and PHP as the server. Client get reported items and distributors data, alarm from items which will expired, stoks charts and can get supplier’s address from maps. All of inputting and editing data is located on the server side. This application could be the one solution for supermarket workers in anticipation of the circulation of expired items.Keywords: Expired date, Android, PHP, Client, Server, Map